2007
DOI: 10.1111/j.1399-6576.2007.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anesthesia for the obese and morbidly obese patient: an ounce of prevention is worth more than a pound of treatment

Abstract: Background: The incidence of obesity has been dramatically increasing across the globe. Anesthesiologists, are increasingly faced with the care for these patients. Obesity in the pregnant woman is associated with a broad spectrum of problems, including dramatically increased risk for cesarean delivery, diabetes, hypertension and pre-eclampsia. A thorough understanding of the physiology, associated conditions and morbidity, available options for anesthesia and possible complications is therefore important for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
0
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(119 citation statements)
references
References 111 publications
(129 reference statements)
2
103
0
13
Order By: Relevance
“…The significantly longer catheter dwell time and insertion at an earlier cervical dilatation, were not associated with extension failure. This result is important, given suggestions by experts and international guidelines, that epidurals be inserted early in labor, for obese women 9, 25, 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significantly longer catheter dwell time and insertion at an earlier cervical dilatation, were not associated with extension failure. This result is important, given suggestions by experts and international guidelines, that epidurals be inserted early in labor, for obese women 9, 25, 26…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) has not been consistently identified as a risk factor for failed epidural extension,7, 8 however, this may be influenced by under‐representation in study populations. The effectiveness of epidural extension in obese women is important to know, as epidurals may be placed with the explicit intention of permitting extension for subsequent cesarean delivery if required 9, 10. Our previous retrospective pilot study found epidural extension was more likely to fail in women with BMI ≥ 40 kg/m 2 11.…”
mentioning
confidence: 99%
“…Both oxygen consumption and carbon dioxide production have linear relationship with body weight. Because of the augmented fat mass in the chest and abdominal walls and the upward retraction of this adipose tissue caused by supine position, respiratory difficulty and even oxygen desaturation can be experienced by the obese pregnant woman as these factors further lower the functional residual capacity, expiratory and inspiratory reserve volumes and chest wall compliance leading to worsening of the V/Q relationship [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increase in operative delivery obese group also have risk of wound infections and thromboembolic events. They also have anesthetic complications like failed intubation 17 . Our study did not show any risk of wound infections or any other post-operative complications.…”
Section: Discussionmentioning
confidence: 99%